A organizacao do curso de direito e a formacao do bacharel: estudo em uma instituição privada na cidade de São Paulo - Ferreira, Gabriela Gomes Coelho (2013)
This study aims to examine the documents which express the pedagogical organization of the course of a law school, private and located in the city of Sao Paulo, as well as other documents that somehow guide this organization (related to the Bar Exam Brazil and also the Curriculum Guidelines for Law courses set by the Ministry of Education). We sought to identify and examine trends present in the process of training of graduates, with reference to the critical theory of society. So interested check for regressive tendencies (that reinforce domination) and those potentially emancipatory. Therefore, the concept of law is discussed and situated as a product of the state and therefore as an expression of political and economic society, which results in the need for training that goes beyond technical expertise and dogmatic. Trend analysis allows us to assert that the ongoing investigation presents an orientation marked by complexity and that there is great interplay between trends that may be considered regressive and potentially emancipatory. An example is how the word "critical" is used: it could be classified as a potentially emancipatory trend, however, as it appears in the text - aligned to efficiency and labor market - and the lack of a more theoretical than makes dubious in significance by not expressing the ideology that carries causes may be allocated among the regressive tendencies: there seems to be an awareness of the necessity of criticism, but does not express exactly what you mean and may even reinforce exactly which aims to break. A decreasing trend seems born that you want to be potentially emancipatory